2021
DOI: 10.1016/j.ajo.2020.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Management Changes at the Postoperative Day One Visit After Pars Plana Vitrectomy for Retinal Detachment

Abstract: Purpose To evaluate the incidence of unexpected management changes on the first day after pars plana vitrectomy for retinal detachment repair Design Retrospective cohort study Participants All cases of pars plana vitrectomy (PPV) for rhegmatogenous or tractional retinal detachment with completed postoperative day one (POD1) and week one (POW1) visits were included. Methods The medical and billing records of a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…of eyes Increase in IOP Intraocular inflammation Hypotony Corneal edema Jabbour et al [ 8 ] 2018 RRD, PDR with tRD, MH 254 48 ~ 61.5% within POD 7 N/A N/A N/A Bamonte et al [ 6 ] 2011 Floater, macular pucker, MH, RD, etc. (VH, retained lens fragments, lens subluxation) 122 N/A N/A 13.1% on POD 1 N/A Arikan Yorgun et al [ 5 ] 2016 ERM, VH, MH, RD, VMT 306 15%~25% on POD 1 5 ~ 26% exhibited more than + 2 AC cells on POD 1 1.8 ~ 2.7% on POD 1 N/A Patel D. et al [ 10 ] 2021 RRD or tRD 418 IOP > 21 mm Hg, 69 eyes (16.5%); IOP > 30 mm Hg, 11 eyes (2.6%) N/A N/A N/A Moussa et al [ 9 ] 2023 Pseudophakic RRD 456 IOP ≥ 22: 28.0 ~ 49.6%, IOP ≥ 25: 13.6 ~ 30.3% on POD 1 N/A 0 ~ 0.8% on POD 1 N/A Desai A. et al [ 25 ] 2008 RD, VH, MH, ERM, retained lens fragments, endophthalmitis, floaters 100 2.5 ~ 12% required IOP control on POD 1 N/A N/A N/A …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of eyes Increase in IOP Intraocular inflammation Hypotony Corneal edema Jabbour et al [ 8 ] 2018 RRD, PDR with tRD, MH 254 48 ~ 61.5% within POD 7 N/A N/A N/A Bamonte et al [ 6 ] 2011 Floater, macular pucker, MH, RD, etc. (VH, retained lens fragments, lens subluxation) 122 N/A N/A 13.1% on POD 1 N/A Arikan Yorgun et al [ 5 ] 2016 ERM, VH, MH, RD, VMT 306 15%~25% on POD 1 5 ~ 26% exhibited more than + 2 AC cells on POD 1 1.8 ~ 2.7% on POD 1 N/A Patel D. et al [ 10 ] 2021 RRD or tRD 418 IOP > 21 mm Hg, 69 eyes (16.5%); IOP > 30 mm Hg, 11 eyes (2.6%) N/A N/A N/A Moussa et al [ 9 ] 2023 Pseudophakic RRD 456 IOP ≥ 22: 28.0 ~ 49.6%, IOP ≥ 25: 13.6 ~ 30.3% on POD 1 N/A 0 ~ 0.8% on POD 1 N/A Desai A. et al [ 25 ] 2008 RD, VH, MH, ERM, retained lens fragments, endophthalmitis, floaters 100 2.5 ~ 12% required IOP control on POD 1 N/A N/A N/A …”
Section: Discussionmentioning
confidence: 99%
“…Modern vitreoretinal surgery is safe and effective in treating various retinal disorders, including rhegmatogenous retinal detachment (RRD), [ 1 ] complications of diabetic retinopathy, [ 2 ] macular hole (MH), [ 3 ] and epiretinal membrane (ERM) [ 4 ]. However, since vitreoretinal surgery is invasive, postoperative complications, such as increased (2.5–61.5%) or decreased (1.8–13.1%) intraocular pressure (IOP), [ 5 10 ] corneal edema (0.80–1.1%) [ 7 , 11 ], intraocular inflammation (0.25–26%) [ 5 , 12 ], or retinal detachments (1.2–1.7%) may occur in patients [ 11 ]. Therefore, the postoperative care plan for patients may be changed according to the type and severity of these complications [ 12 ].…”
Section: Intruductionmentioning
confidence: 99%
“…These findings are consistent with similar large-scale retrospective investigations. For example, the study by Patel et al [20] , involving 418 cases, reported a 16.5% incidence of elevated IOP, and Arikan Yorgun et al's [21] study, based on 306 cases, showed that 15%-25% of patients showed elevated IOP. None of these participants reported severe pain, or were found to have hypotony or epithelial defects.…”
Section: Perfluoro-n-octane In Retinal Detachmentmentioning
confidence: 99%
“…Short-term complications following surgery have been widely reported in patients with ERM [ 9 , 10 ]. Datlinger et al reported postoperative movement of the fovea one day after successful surgery for iERM [ 11 ].…”
Section: Introductionmentioning
confidence: 99%